PREAGRIoT: Precision Agriculture IoT Monitoring And Controlling System - Abang Othman, Dyg Khayrunsalihaty Bariyyah; Mai, Caroline Ann; Ibrahim, Abdul Yazid (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2022)
Precision agriculture is an emerging technology in Malaysia. It is a remote sensing-based technique combined with analysed data and relevant information to support management in optimizing and sustaining agricultural productivity. The yield of various agricultural products can be influenced by few factors such as the condition of soil, temperature, humidity, and weather. Traditional farming often requires a human presence on the site to monitor the ideal surrounding and this may consume time and money. Thus, a precision agriculture for monitoring and controlling system (PREAGRIoT) is introduced to overcome this problem. PREAGRIoT is a system that integrates a free custom Telegram bot with an open-source Internet of Things (IoT) platform called NodeMCU ESP8266. It is specifically designed to monitor temperature and humidity by using a BME280 sensor. PREAGRIoT can control any electrical appliances for remote intervention at the monitored area. A test-bed of the prototype reveals the ability of PREAGRIoT to sense changes of temperature and humidity precisely at 2 decimal places and easily switch on any electrical output.